The Concept of Complete Systematic Land Registration (PTSL) in Providing Legal Certainty Guarantees to Land Rights Holders - Anna Martina Anggitasari; Made Warka; Sjaifurrachman Sjaifurrachman (International Journal of Sociology and Law, 2025)
This study aims to identify and analyze the ratio legis of the principle that the Complete Systematic Land Registration (PTSL) program needs to be regulated and adhered to. Furthermore, this research also seeks to examine the legal consequences of the Complete Systematic Land Registration (PTSL) program. The awareness of the special position of land in the Indonesian national consciousness is also revealed in the Basic Agrarian Law (UUPA), which states the eternal relationship between the Indonesian people and the land. However, the term “controlled” in Article 33 of the 1945 Constitution does not imply that the state is the owner. The general explanation of the 1960 UUPA clarifies that the state (government) only controls the land. The meaning of land being “controlled” does not equate to “owned” but rather refers to certain authorities granted to the state as a power organization. Ownership of land rights must be proven by authentic or valid evidence in the form of a land rights certificate, where such certified ownership is an absolute requirement. Therefore, the Indonesian Government, through the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018 concerning Complete Systematic Land Registration, aims to facilitate the implementation of systematic and complete land registration as a government program. From this explanation, it can be concluded that the ratio legis of the Complete Systematic Land Registration (PTSL) program principle requires regulation and adherence to provide guarantees of legal certainty, transparency of information related to land parcels that can be utilized by legitimate parties, and ensure orderly administration in the field of land affairs, thereby delivering benefits and justice.